Highly efficient NIR to NIR upconversion of ZnMoO4:Tm3+, Yb3+ phosphors and their application in biological imaging of deep tumors. Issue 37 (2nd September 2016) - Luitel, Hom Nath; Chand, Rumi; Hamajima, Hiroshi; Gaihre, Yuba Raj; Shingae, Takahito; Yanagita, Teruyoshi; Watari, Takanori
Abstract : In vivo imaging of deep tumor in nude-mice was successfully demonstrated using highly efficient ZnMoO4 :Tm 3+, Yb 3+, K + nano-phosphors and an 810 nm NIR laser. Abstract : ZnMoO4 :Tm 3+, Yb 3+, K + nano-phosphors with intense NIR to NIR (excitation by 980 nm, emission at ∼800 nm) upconversion were synthesized by a facile hydrothermal method. The nanoparticles were of the order of 200–400 nm. The XRD patterns confirmed a single phase triclinic structure despite doping small amounts of RE 3+ and alkali ions. The optimum concentration of Tm 3+, Yb 3+ and alkali ions were determined to be 0.1 mol%, 10 mol% and 10 mol%, respectively. Besides charge neutrality, the doped K + ions affected the crystal field symmetry around the Tm 3+ ions which increased the f–f transition probabilities of the RE 3+ ions, and hence increased the UC intensities. Compared with ZnMoO4 :Tm 3+, Yb 3+, the NIR to NIR upconversion emission intensity of 10 mol% K + substituted ZnMoO4 :Tm 3+, Yb 3+ nanocrystals increased by 21-fold and can be pumped by less than 1 mW laser power. The brightest ZnMoO4 :Tm 3+, Yb 3+, K + nano-phosphor was applied for non-invasively visualizing the tumors in nude mice and successfully detected deep tumors in the thigh muscles. So far, this is the first report of oxide based UCNPs used for in vivo NIR-to-NIR biological imaging and opens the door to the possibility of achieving improved features using non-fluoride based UCNPs.